2018
DOI: 10.1136/bmj.k1497
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of diagnosed type 1 and type 2 diabetes among US adults in 2016 and 2017: population based study

Abstract: ObjectiveTo estimate the prevalence of diagnosed total diabetes, type 1 diabetes, and type 2 diabetes in the US general population and the proportions of each among US adults with a diagnosis of diabetes.DesignNationwide, population based, cross sectional survey.SettingNational Health Interview Survey, 2016 and 2017.ParticipantsAdults aged 20 years or older (n=58 186), as a nationally representative sample of the civilian, non-institutionalized US population.Main outcome measuresPrevalence of diagnosed diabete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
281
3
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 414 publications
(303 citation statements)
references
References 41 publications
12
281
3
7
Order By: Relevance
“…Although the number of women diagnosed with type I diabetes was small, this is reflective of the general population which is expected to have very low type I diabetes prevalence (0.6%, 95%CI ¼ 0.5, 0.8) among individuals 45 years. Specifically, they reported that the weighted prevalence (%, 95%CI) for type I diabetes were 0.5 (0.3, 0.6), 0.6 (0.4, 0.7), and 0.6 (0.5, 0.8) in 20e44 aged, 45e64 aged, and 65 aged adults in the United States [34].…”
Section: Discussionmentioning
confidence: 99%
“…Although the number of women diagnosed with type I diabetes was small, this is reflective of the general population which is expected to have very low type I diabetes prevalence (0.6%, 95%CI ¼ 0.5, 0.8) among individuals 45 years. Specifically, they reported that the weighted prevalence (%, 95%CI) for type I diabetes were 0.5 (0.3, 0.6), 0.6 (0.4, 0.7), and 0.6 (0.5, 0.8) in 20e44 aged, 45e64 aged, and 65 aged adults in the United States [34].…”
Section: Discussionmentioning
confidence: 99%
“…Although it was not possible to accurately distinguish between type 1 and type 2 diabetes, more than 98% of those classified with diabetes had at least one code indicating type 2 diabetes. Also, the prevalence of type 1 diabetes among older adults is less than 4%, and prior studies of veterans have documented low prevalence of true type 1 diabetes because this diagnosis disqualifies military service …”
Section: Discussionmentioning
confidence: 99%
“…Also, the prevalence of type 1 diabetes among older adults is less than 4%, and prior studies of veterans have documented low prevalence of true type 1 diabetes because this diagnosis disqualifies military service. (27,28) Our study has several strengths. To our knowledge, this is the largest cohort study among older men with diabetes investigating the association and interactions of glycemic control and treatment regimen on incident fracture risk.…”
Section: Journal Of Bone and Mineral Researchmentioning
confidence: 96%
“…Compelling observational epidemiological studies have shown that NAFLD is highly correlated with metabolic disorders such as type 2 diabetes (T2D) [3][4][5] and obesity 1,6,7 . All three diseases together affect over 50% of the U.S. population [8][9][10] .…”
Section: Introductionmentioning
confidence: 99%